Liquid biopsies and those three little words: finding the perfect match for the MTB - Wahida, Adam; Buschhorn, Lars (Medizinische Genetik, 2023)
Monitoring ctDNA by liquid biopsies seems to represent the perfect match for precision oncology and its cornerstone clinical framework: the molecular tumour board (MTB). Detecting and scrutinising the success of targeted therapies or tracking and, for that matter, addressing the therapy with the evolutive nature of a tumour are some of the main advancements one considers to be important for the MTB. One challenge is correlating the estimated allele frequency of each identified genetic alteration determined by analysing the ctDNA sequencing results and matching these with the range of suitable drugs, which may limit the simultaneous treatment of all tumour variations. This limitation arises because a new biopsy would typically be required to evaluate the response to treatment. As a result, evaluating the success of MTB recommendations relies on traditional staging methods, highlighting an existing diagnostic gap. Thus, optimising liquid biopsy technology could enhance the efficacy of MTB treatment recommendations and ensuing tailored therapies. Herein, we discuss the prospect of ctDNA analyses in the molecular tumour board.
Gesehen am 11.11.2024